PENGGUNAAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR MATERI MERODA PADA SENAM LANTAI KELAS VIII SMP NEGERI 13 SEMARANG TAHUN 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the improvement of teaching physical education in schools through the use of audio-visual media aids the learning outcomes gymnastics floor meroda the eighth grade students of SMP Negeri 13 Semarang. In this research, a classroom action research (CAR ) cycle , the study was conducted in two cycles of action . Methods of data collection using the methods of documentation , observation , and testing . Analysis of the data using descriptive method by way of student learning outcomes after the action . Based on the results obtained by the use of audio-visual media in the learning material meroda floor exercises can improve learning outcomes eighth grade at Junior High School 13 Semarang 2013/2014 . This is evidenced by the acquisition value of the learning outcomes of each cycle has increased . The average value of students in the first cycle the average test score of students reached 70.51 , reaching 84.72 in the second cycle . Classical completeness in the first cycle of 54.84 % and the second cycle was 90.32 % . From the research results obtained it can be concluded that the learning material meroda floor exercises with the use of audio-visual media can improve learning outcomes students of SMP Negeri 13 Semarang .